ANALISIS NILAI-NILAI PENDIDIKAN AKIDAH DALAM KITAB AUJAZUL MUKHTASHARAT KARYA IMAM AL-FAQIH ASY-SYAIKH ABDUL AZIZ BIN IBRAHIM AR-RAYYI AL-HABASYI - Siti Aisyah; Azizah Hanum OK (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the values of faith education contained in the book Aujazul Mukhtasharat by Imam Al-Faqih Asy-Syaikh Abdul Aziz bin Ibrahim Ar-Rayyi Al-Habasyi. The research method used is qualitative with a library research approach. Data were obtained from primary data sources, namely the book Aujazul Mukhtasharat published by Sheikh Abdullah bin Ibrahim in 2017, and secondary data sources, namely books and journal articles. The results of the study show that this book contains fundamental faith values, namely faith in Allah, because the most important obligation is to believe in Allah and His Messenger and the most severe (dangerous) kufr is at-ta'thil (denying the existence of Allah) and the worst is riddah. Then faith in angels, His books, the messengers, the last day, and qadha and qadar. The presentation of the material in this book is very concise, dense, and clear, making it easy for students at various levels to understand. Therefore, the book Aujazul Mukhtasharat is highly recommended for use in educational institutions as a teaching material for faith, because it is able to convey the concepts of faith systematically and effectively.